Impact of Climate Variabilty on Water Resources And Population Health in the South Eastern Coastal Area of Côte d’Ivoire - Gautier, Kpan Oulai Jean; Marie-Solange, Oga Yei; Theodore, Yao Koffi; Fabrice, Yapi Assa; Derving, Baka; Theophile, Lasm; Jean, Biemi (European Scientific Journal, ESJ, 2016)
The present study evaluates the impact of climate variability on water resources and population health in the coastal area of Cote d’Ivoire between Abidjan and Aboisso. First, hydroclimatic methods (Nicholson index) and statistical tests (Pettitt test, Hubert segmentation) were used for variability characterisation. Then, Thornthwaite Water balance method was used to evaluate water availability for aquifers recharge. Coefficient depletion method was also used to assess the impact of climate variability on surface water resources. The relationship between diseases occurence (AhigbeKoffikro and Samo) and rainfall pattern was evaluated through descriptive method. The results revealed important fluctuations of water resources levels at that time. The relationship rainfall-runoff showed with synchron trend that rivers flows regime was linked to rainfall. The impact on groundwater resources was explained by deficit of infiltrated water of about 35.49% and 22.61% after 1982 break at Abidjan airport and Bingerville stations respectively. Concerning health, 63% of malaria cases was observed against 2.85% for diarrhoea and 2.35% for helminthiasis. There was a strong relationship between rainfall and the diseases (malaria and diarrhoea).